Dental implants in Sjögren’s syndrome patients: A systematic review - Almeida, Daniel; Vianna, Katia; Arriaga, Patrícia; Moraschini, Vittorio (PloS one, 2017)
The Sjögren's syndrome (SS) is a chronic autoimmune disease that affects salivation and consequently the health of oral tissues. The aim of this systematic review was to investigate the implant survival rate, marginal bone loss (MBL) and biological complications of dental implants in SS patients. Eligibility criteria included prospective and retrospective cohort studies, controlled clinical trials, and randomized clinical trials (RCTs). An electronic search without date or language restrictions was carried out in MEDLINE, Cochrane, Web of Science, and LILACS until June 2017. In addition, manual search and in the grey literature were also conducted. The search process, data analysis, and quality assessment were performed by two independent reviewing authors. The protocol of this systematic review was registered in PROSPERO under number CRD42016053277. The search and selection process yielded 6 studies, published between 1997 and 2016. An average of 93.7% survival in a mean period of 3.97 years of follow-up was observed. A low number of MBL and biological complications were reported by the studies. All the studies analyzed observed an improvement in life quality of subjects with SS and rehabilitated through dental implants. With the limitations of this review and based on the available data, the dental implant therapy in SS patients seems to present high implant survival rate, low MBL and low biological complications. In addition, all included studies observed an increase in the quality of life of SS patients who were rehabilitated through dental implants.